THE IMPLEMENTATION OF SOLID WASTE REGULATION IN PD KEBERSIHAN OF BANDUNG CITY: KNOWLEDGE MANAGEMENT ANALYSIS - Anih Sri Suryani (Widyariset, 2012)
Solid waste management is a problem should be concerned in Bandung City. The enactment of Law No. 18of 2008 on Solid Waste Management constitute as it’s the legal basis. Implementation of this law was analyzedin frameworks of knowledge management in PD Kebersihan of Bandung City. Result of the study indicated thatknowledge management related to solid waste management made by a kind of method equipment, which has acreation activity phase and high level process. Agents who worked to transfer the knowledge were an organizationusing explicit artefact. Whereas the focus activity was on artefact.